Coupling the treatment of low strength anaerobic effluent with fermented biowaste for nutrient removal via nitrite. (1st February 2015) - Katsou, E.; Malamis, S.; Frison, N.; Fatone, F.
Abstract: Nutrient removal via nitrite was investigated in a sequencing batch reactor (SBR) treating low strength effluent produced from an upflow anaerobic sludge blanket (UASB). Domestic organic waste (DOW) and vegetable and fruit waste (VFW) were fermented and applied as external carbon source to the SBR. Nutrient removal via nitrite was much higher when DOW fermentation liquid (FL) was applied rather than VFW FL and acetic acid. The DOW FL contained propionic acid and butyric acid in significant proportions, favouring the nutrient removal via nitrite, while the VFW FL contained mainly acetic acid, which was associated with lower nutrient via nitrite activity. The application of high volumetric nitrogen loading rate (vNLR = 0.19–0.21 kgN m −3  d −1 ) in combination with low dissolved oxygen (DO) concentration during the aerobic phase, resulted in high and stable nitrite accumulation (NO2 –N/NOx –N >97%). These conditions favoured the phosphorus uptake via nitrite, which reached high rates (5.95 ± 2.21 mgP (gVSS h) −1 ), while the aerobic phosphorus removal was much lower. Through mass balances, it was demonstrated that the application of the UASB-SBR process with nutrient removal via nitrite at a decentralized level is a sustainable solution for effective co-treatment of domestic sewage and biowaste. Graphical abstract: Highlights: UASB-SBR via nitrite is feasible for sewage and biowaste co-treatment. Biowaste fermentation liquid enhances denitrification and phosphorus uptake rates. High vNLR and low DO resulted in complete nitrite accumulation.